Randomized clinical trial of percutaneous transluminalangioplasty, supervised exercise and combined treatment forintermittent claudication due to femoropopliteal arterial disease - Mazari, F. A. K.; Khan, J. A.; Carradice, D.; Samuel, N.; Abdul Rahman, Mohd Norhisham Azmi; Gulati, S.; Lee, H. L. D.; McCollum, P. T.; Chetter, I. C. (Wiley Online Library, 2012)
Background:The aim was to compare percutaneous transluminal angioplasty (PTA), a supervisedexercise programme (SEP) and combined treatment (PTA plus SEP) for intermittent claudication dueto femoropopliteal arterial disease.Methods: Consenting patients with femoropopliteal arterial lesions were randomized to one of threetreatment arms: PTA, SEP, or PTA plus SEP. All patients received optimal medical treatment. Patientswere assessed at baseline and 1, 3, 6 and 12 months after intervention. Clinical (ankle pressures, walkingdistances, symptoms) and quality-of-life (QoL) outcomes (Short Form 36, VascuQol) were analysed.Results: A total of 178 patients (108 men, median age 70 years) were included. All three treatmentgroups demonstrated significant clinical and QoL improvements. One year after PTA (60 patients, 8withdrew), 37 patients (71 per cent) had improved (16 mild, 16 moderate, 5 marked), nine (17 per cent)showed no improvement and six (12 per cent) had deteriorated. After SEP (60 patients, 14 withdrew),32 patients (70 per cent) had improved (19 mild, 10 moderate, 3 marked), six (13 per cent) showed noimprovement and eight (17 per cent) had deteriorated. After PTA plus SEP (58 patients, 11 withdrew),40 patients (85 per cent) had improved (18 mild, 20 moderate, 2 marked), seven (15 per cent) showedno improvement and none had deteriorated. On intergroup analysis, PTA and SEP alone were equallyeffective in improving clinical outcomes, although the effect was short-lived. PTA plus SEP produced amore sustained clinical improvement, but there was no significant QoL advantage.Conclusion: For patients with intermittent claudication due to femoropopliteal disease, PTA, SEP,and PTA plus SEP were all equally effective in improving walking distance and QoL after 12 months.Registration number: NCT00798850 (http://www.clinicaltrials.gov).